Bilingualisme Masyarakat dalam Wacana - Saefuddin Saefuddin (Buletin Al-Turas, 2005)
The expectation to be fluent bilinguals in English, Arabic, and Indonesian is the main target at the elementary, junior, and senior high schools or madrasahs. At the university, it becomesfluent bilinguals as we have to know the local language as well. At the elementary level, pupils are taught through the contextual language instructing approach, connected with the real world activities such as taking part in environmental awareness and Indonesian's diverse ethnic groups. The approach at the junior high schools is then connected with classroom-based and task-based approach by increasing the competency skills with daily life activities as in writing a report, etc. Hopefully, at the academic level, students are trained to improve their language skills, providing chances to use English or Arabic in real communication, and exposed to many topicsand issues related to the environment.